PENGARUH PELAYANAN TERHADAP KEPUASAN NASABAH (Kasus pada PT Bank Mandiri Cabang Makassar Sulawesi) - Adam Salehe (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
This Research aim to know how far influence of service quality given by Self-Supporting PT Bank (Persero). Branch the Makassar Sulawesi to its client. Population in this research is all Self-Supporting Bank client Branch The Makassar Sulawesi. Intake Sampel in this research is done by using approach of is non random sampling with the technique exhaustive, in this case in taking sampel as much 50 client people as research responder. Technique analyse the data weared by is doubled linear regression. Result of research indicate that the overall of form of dimension of service quality (reliability, responsiveness, assurance, empathy and tangible) signifikan influence the client satisfaction, where dimension assurance as dominant service quality dimension influence the client satisfaction. Its meaning, employees PT. BRI (Persero) Tbk. Branch The Makassar